Promouvoir la compréhension écrite à travers les médias en ligne 1jour1actu : cas des élèves de SMA N 9 Bandar Lampung - Balqis, Tsabitha; Rosita, Diana; Nevira Trisna, Indah (Universitas Negeri Semarang, 2025)
This study aimed to determine the difference in French language comprehension ability among students in class XII of SMAN 9 Bandar Lampung before and after using the 1jour1actu media. The research subjects were the students in class XII 8, 35 students in total, who constituted the experimental class. This research is a quantitative study with a single-group pre-test-post-test research design. In this study, the t-test, N-gain, normality, and homogeneity tests were used with the help of SPSS 22 to analyze the data. The results showed that the pre-test mean was 68.57 while the post-test result was 83.57. There was an increase of 15 points. In addition, the t-test value was obtained with a significant value of 0.000. The advantages of 1jour1actu learning materials are that students become more enthusiastic, have no trouble finding materials to practice reading comprehension at school and home, and can improve their knowledge of French vocabulary. The disadvantages of 1jour1actu learning media are that the material provided is too complex and not focused on a single subject. In addition, students have difficulty using 1jour1actu when the signal is unstable.